UPAYA PENINGKATAN PENGETAHUAN MELALUI TEMU TUGAS PENELITI – PENYULUH DI PROVINSI SULAWESI TENGAH - Herawati Herawati; Asnidar Asnidar; Saidah Saidah (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2021)
This research is entitled Efforts to Increase Knowledge through a Researcher-Extension Team in South Sulawesi Province. The objectives of this study were 1) to find out the technical and economic knowledge of researchers - Balitbangtan extension agents - Local Government about the material presented. 2) Exploring feedback on the application of technology from the BPTP assessment that has the potential to be developed in potential areas. 3) Increasing promotion, technology transfer, dissemination, adoption of innovation/ technology package results from the BPTP assessment and coordination of the implementation of joint tasks, and 4) Inventory of responses / opinions of training participants on the implementation of training. This research method used a questionnaire survey method to the task meeting participants, then the data obtained were analyzed descriptively and continued with the Wilcoxon Match Pairs Test. The Wilcoxon Match Pairs Test shows that the asymp.sig (2-tailed) value of 0.000 is smaller than 0.05, so it can be concluded that training has an effect on increasing extension knowledge of the materials provided at the Balitbangtan-Government Research and Development Gathering. Regional (Pemda), namely an increase in the knowledge of participants after the Task Meeting meeting was held.